How well do conservation auctions perform in achieving landscape‐level outcomes? A comparison of auction formats and bid selection criteria1. (29th August 2017) - Iftekhar, Md Sayed; Latacz‐Lohmann, Uwe
Abstract : This paper studies the performance of auction design features regarding pricing mechanisms and bid selection criteria for securing wildlife zones across different holdings. We compare two pricing mechanisms: a discriminatory‐price auction and a uniform‐price ascending auction, and four bid selection criteria on the basis of: total bid, bid‐per‐value ratio, bid‐per‐area ratio and a mixed criterion where bids are formed on the basis of cost but they are selected based on the bid‐per‐value ratio. We develop a best‐response group‐bidding model for a discriminatory‐price auction where bidders form optimal group bids for individual wildlife zones. In the uniform‐price ascending auction, individual landholders respond to prices, which are successively raised by the auctioneer and whenever all the landholders from a single zone agree to participate (i.e. the first zone is formed), the auction stops. Based on numerical simulations using a bio‐economic model of malleefowl conservation, we observe that the discriminatory‐price auction is more cost‐effective than the uniform‐price ascending auction. However, the budgetary cost‐effectiveness of a discriminatory‐price auction is sensitive to bidder uncertainty about the number of competing bidder groups and the highest cost of establishing a wildlife zone among these groups. In terms of bid selection, the mixed bid selection criterion performs best. We discuss the policy implications of these findings.